Mental Health Promotion for the ‘In-Betweeners’: The Rationale and Effectiveness of Community-Based Mentoring and Coaching Schemes for Primary School-Aged Children. - Anna McKinnon; Ian Hickie; Jan Scott (Journal of Preventive Medicine And Care, 2017)
Background: There are relatively few research publications of mental health promotion initiatives for primary school aged children that are based in community rather than educational settings. Aims: To describe developmental frameworks and models of mentoring, coaching and mental health promotion and to summarize any evidence for the efficacy of community initiatives. Methods: An umbrella review was undertaken of publications on theories and models, and a synthesis of findings from reviews of outcomes of mentoring, mental health promotion initiatives undertaken outside of school time for children aged 5-11 years. Results: Developmental mentoring on its own or in combination with outside school activities is potentially more flexible in terms of delivery and targets than school-based programs. Pooled effect sizes (range about 0.2-0.4) suggest modest but significant gains across several key domains (cognition, emotion, physical health, and social connectedness) that equate to about 10 percentile point on the developmental evaluations employed. Mediators of benefits include the level environmental or individual risk of the child and parental involvement. It is noteworthy that poor quality, atheoretical programs can have detrimental effects. Conclusions: Children aged 5-11 years may be more accepting of, and could make significant gains from, community-based mental health promotion interventions such as developmental mentoring. However, there are some significant gaps in the knowledge-base that need to be addressed through more systematic research.
Keywords: mentoring